2020
DOI: 10.1002/1873-3468.13734
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of nonglycosylated forms of N‐glycoprotein upon proteasome inhibition does not confirm cytosolic deglycosylation

Abstract: N‐Glycosylated substrates that undergo ER‐associated degradation (ERAD) are often deglycosylated by the cytosolic peptide:N‐glycanase (Ngly1) during their proteasomal degradation in the cytosol. Consequently, the presence of non‐ or deglycosylated forms of such proteins after treatment with proteasome inhibitors is widely used as evidence for cytosolic deglycosylation by Ngly1. However, in this study, the accumulation of nonglycosylated RTA∆m, a model ERAD substrate, was still observed in mouse cells lacking c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…To validate this hypothesis, we treated rat primary hepatocytes with NGI-1, a known cellular inhibitor of OST activity ( 33 ). It has previously been shown that this compound inhibits the release of FNGs in Ngly1 –/– Engase –/– mouse embryonic fibroblast cells ( 38 ). Our results showed that the NGI-1 treatment indeed significantly decreased the amount of Gn2-type sialyl FNGs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate this hypothesis, we treated rat primary hepatocytes with NGI-1, a known cellular inhibitor of OST activity ( 33 ). It has previously been shown that this compound inhibits the release of FNGs in Ngly1 –/– Engase –/– mouse embryonic fibroblast cells ( 38 ). Our results showed that the NGI-1 treatment indeed significantly decreased the amount of Gn2-type sialyl FNGs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The gradient program was as follows: 0 to 0.5 min, 1 to 10% eluent B; 0.5 to 45 min, 10 to 55% eluent B; 45 to 47 min, isocratic 70% eluent B; and 47 to 67 min, isocratic 1% eluent B. The jack bean α-mannosidase-sensitive peaks, collected from dual gradient reversed phase HPLC, were further separated in the same column and eluent A/B using a previously reported program ( 38 ).…”
Section: Methodsmentioning
confidence: 99%